Asuhan Keperawatan Keluarga Dengan Anak Mengalami Epilepsi Pada Masa Pandemi Covid 19 Di Kecamatan Dawarblandong Kabupaten Mojokerto - Siti Rachmah, S.KM., M.Kes; Dini Aliyah (Sekolah Tinggi Ilmu Kesehatan Majapahit Mojokerto, 2021)
Epilepsy is a manifestation of brain function disorders with various etiologies and with a single characteristic symptom, namely recurrent seizures due to excessive and paroxysmal electrical discharge of brain neurons. Seizures often occur in epileptic children younger than 15 years. Children with epilepsy have a high risk of developmental delays, physical accidents, learning problems, cognitive delays, social problems, difficulty being independent and being a burden to their families and environment. Families play an important role in healing in children with epilepsy. The purpose of writing is to determine family nursing care for children with epilepsy which includes assessment, intervention, implementation and evaluation of nursing. The research method is descriptive or a description of a case. The results of this scientific paper are that after 3 visits, the family understands and is able to state the meaning, causes, signs and symptoms and the first treatment at the time of seizures, the family is also able to mention things that can trigger seizures and the family can apply how to treat seizures. Family support is needed for the success of nursing care for children